PEMANFAATAN MEDIA ONLINE SEBAGAI SARANA EDUKASI KESEHATAN PADA REMAJA : TINJAUAN LITERATUR - Surya Dwi Sembada; Hadi Pratomo; Ida Fauziah; Syahidah Asma Amani; Queen Nazhofah; Riska Kurniawati (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
The development both technology and internet lead to Industry 4.0 that affect various sector, including education and health sector. The emergence of COVID-19 as pandemic since the end of 2019 has increasingly demanding practice of Education 4.0. This was reinforced by the implementation of health protocols such as wearing mask when leaving the house, diligently washing hands with soap with running water, and physical distancing. As a consequence, mass to conduct direct health education is difficult.Â  The purpose of the study is to provide an overview of the effectiveness of online media to educate adolescents during pandemic COVID-19. This study is a literature review search from electronic database, such as Google Scholar, Springer, and Sciencedirect. Certain inclusion criteria were performed including a keyword of health education through online media. There were 10 articles from electronic database that published from 2014 â€“ 2020. This covered both in Indonesian and English language. WhatsaApp, Google Meet, Zoom, or website are used for intervention. The majority of the literature uses questionnaire, online or offline, to assess the increase in knowledge before and after the intervention. The conclusion indicated the effectiveness of online media in health promotion in increasing knowledge, attitudes, and healthy behavior among adolescents. Â